Popkulturowe reprezentacje futbolu w piłkarskich powieściach kryminalnych = Pop culture representations of football in football crime novels - Stadnik, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is an attempt to characterize a new subgenre of crime fiction - the football thriller. The author presents the relationships between the genre and popular culture, showing the influence of football on modern culture and literature. The article presents the realizations of the subgenre in Europe as well as its Polish version and compares novels written by professional writers and by journalists.
Keywords: powieść kryminalna; thriller piłkarski; literaturoznawstwo